ADVERSITY QUOTIENT LEVEL FOR WRITING OUTPUT (A Case Study in Pertamina Lubricant) - Yuliana Ambarsari (Pendidikan Bahasa Inggris STKIP Nurul Huda, 2017)
Even so far was found rare interference between Adversity Quotient and academic result, some researchers do investigating how it affects either academic process or its result. Inasmuch the way some investigate it quantitatively, this study was aimed to find out if there was connection between Adversity Quotient of employees toward their writing output qualitatively by purposeful sampling. Data was taken in an English in-house training in Hotel Dreamtel Jakarta in November last year. Two out of six in-house training sessions in Pertamina Lubricants were held to recall participants’ extensive writing ability by displaying examples and doing choral discussion. Then guided questions as stimuli were led, for the participants were able to decide the topic and develop it extensively. Samples were taken to find the highest and the lowest Adversity Quotient score of all participants. Data analysis was done by comparing two scaling styles of Brown-Bailey and Jacob’s. Analytic scoring is done to find out weaknesses and to capitalize strengths. The two scales of Brown-Bailey and Jacob’s consisted of organization, content, grammar, punctuation and style were then figured outand compared (intra-sample and inter-samples). The result shows that Adversity Quotient is not affecting content, grammar, punctuation and style score; somehow, it affects organization development score of participants in some way.